Analysis of the Relationship between the Location of the Anterior Ethmoid Artery and Keros Classification. (28th March 2017) - Poteet, Perry S.; Cox, Matthew D.; Wang, Ran A.; Fitzgerald, Ryan T.; Kanaan, Alissa
Abstract : Objective: We sought to identify a relationship between skull base height and anterior ethmoid artery (AEA) anatomy. Study Design: Retrospective radiologic chart review. Setting: University of Arkansas for Medical Sciences. Subjects: Patients seen in a tertiary rhinology clinic between September 2014 and October 2015. Methods: Review of 101 maxillofacial computed tomography scans with institutional review board approval. Skull base height and AEA locations were measured on each side. Prevalence of the AEA outside of the skull base and distance of the AEA from skull base were calculated and compared with Keros classification using χ 2 testing. Comparisons of skull base height between sexes and age and distance between skull base and the AEA among Keros 2 and Keros 3 patients were made using an unpaired, 2‐tailed t test. Results: The AEA was located below the skull base in 25.7% of cases and more often in Keros type 3 (55%) than in Keros type 2 (29.5%) or Keros type 1 (0%) ( P <. 05). Male patients were significantly more likely to have a greater average skull base height (5.25 vs 4.28 mm) and to have AEAs below the skull base (38.4% vs 14.8%). In addition, the distance of the AEA from the skull base was significantly higher in Keros type 3 patients compared with Keros type 2 patients (4.55 vs 3.42 mm, P =. 001). Conclusions: Variations in the AEA pathway occur more in male patients and those with higher Keros classifications. The distance between the variant AEA and the skull base increases with higher Keros classification. Keros classification can yield insight to the location of the AEA.